The Influence of Motivation and Study Habits on Student Achievement Index - Juandi, Dadang; Monariska, Erma; Tupamahu, Pieter Zakarias (PRISMA, 2025)
This study analyzes the direct and indirect effects of learning motivation and learning habits on student grade point average (GPA). The study used a quantitative approach with the path analysis method. The research sample consisted of 57 students and was obtained based on the distribution of research questionnaires. The results showed some important findings: First, learning motivation has a significant direct influence on learning habits, with a path coefficient of 0.673, indicating the critical role of Motivation in shaping positive learning patterns. Second, learning motivation was also shown to significantly influence the GPA with a path coefficient of 0.498, confirming its role as a key factor in academic achievement. Thirdly, learning habits did not considerably affect the GPA, with a path coefficient of only 0.253. Furthermore, it was found that learning habits did not play an effective role as a mediator in the relationship between learning motivation and grade point average. The practical implications of this study suggest that strategies to improve students' academic achievement should focus more on strengthening learning motivation without neglecting the importance of forming positive learning habits.